Troubling histories: Re-viewing documentary production and surveillance through the Freedom of Information Act. (September 2019) - Grinberg, Daniel
This article examines the variety of risks that critical independent filmmakers have confronted to expose government abuses. It considers the threats to the documentarians and their documents, as they chronicle incidents of state surveillance while they are themselves under state surveillance. It does so by constructing an alternative production history of Laura Poitras' (2014) documentary film Citizenfour in relation to the antecedent case of Emile de Antonio, Mary Lampson, and Haskell Wexler's 1976 film Underground (Whitney Museum of American Art, 2016). These production histories are primarily based on the Freedom of Information Act (FOIA) files that the filmmakers extracted from the US government agencies that targeted them. The article argues that these official files provide an under-explored vantage on the logistical and affective dimensions of making a dissident film. In addition, this article re-views the films the documentarians created under precarious labour conditions to investigate how state intimidation and interference perceptibly impacted these archival records. It examines how the mechanisms of censorship and filmmakers' counteractive security measures registered significant visible traces in the films. Consequently, it argues that the troubling histories captured in both the files and the films can also trouble the authority of official historiography.